Histopathology of liver, kidney, intestine, spleen, and bile of catfish with Jaundice - Farhan Asrido; Sri Nuryati; Widanarni Widanarni (Jurnal Akuakultur Indonesia)
Jaundice is a disease that can affect catfish, resulting in low or unsalable selling prices. The yellow colour in catfish is associated with tissue/organ disorders, particularly bile or liver function. This study aims to compare the histopathological structure of the liver, kidney, intestine, spleen, and bile of naturally jaundiced catfish and those injected with bacteria associated with jaundice. The study employed the observation method, using three variables: healthy catfish as a control (K), yellow catfish treated with Aeromonas spp. bacteria associated with jaundice (KP), and yellow catfish from the farm (KL). The results of the observation showed that the field scale variable (KL) had a higher level of necrosis damage in each organ compared to the laboratory scale variable (KP). The yellow colour in catfish is caused by disrupted organ tissue, particularly in the bile or liver. This can be observed in the liver, intestines, kidneys, spleen, and bile, where the field variable consistently indicates high levels of necrosis damage, with scores ranging from 1.11 to 2.48. Some of these scores indicate moderate damage, with a necrosis percentage of 40% ≤ P < 60% in the liver, kidneys, and bile organs.